Strategi Guru dalam Menanamkan Kedisplinan Shalat Dzuhur Berjamaah pada Siswa SMA Pertiwi 1 Padang - Ramadhan, Defri; Satria, Rengga (ALSYS, 2023)
This research is motivated by the current reality in which there are many negligence among teenagers in carrying out prayer services. Therefore, schools must have the habit of praying in congregation, so that the younger generation instills good habits from an early age. This study focused on the teacher's strategy in instilling the discipline of the congregational midday prayer at Pertiwi 1 Padang High School with the following problem formulation: 1) The teacher's strategy in instilling the discipline of the congregational midday prayer in Pertiwi 1 Padang High School students 2) Supporting factors and inhibiting factors of Islamic religious education teachers in increasing the discipline of students in carrying out congregational prayers. To achieve this goal using qualitative methods with a descriptive approach. This research was conducted at SMA Pertiwi 1 Padang. Data collection techniques used are observation, documentation and interviews. The results of this study indicate that: (1) The teacher's strategy is to provide positive reinforcement by giving value as a form of appreciation in the discipline of congregational prayers and also giving punishment to students who are not disciplined in carrying out congregational midday prayers (2) Supporting factors for teachers in disciplining midday prayers in congregation, namely the existence of a mosque near the school and the existence of school policies. And the inhibiting factors for Islamic Religious Education teachers in disciplining congregational midday prayers are inadequate facilities and infrastructure and a lack of awareness of students to carry out congregational midday prayers.